Writing a project proposal: addendum to development of diabetes register series - Nwose, Ezekiel U. (International Journal Of Community Medicine And Public Health, 2019)
The summary of the series on development of diabetes register in low-mid income country indicated that there is capacity for diabetes services in every hospital, but quality of service needs to improve at all tiers of the healthcare system. The “need to develop proposal for healthcare service improvement” was highlighted.